Application and characterization of magnetic chitosan microspheres for enhanced immobilization of cellulase. Issue 6 (1st November 2016) - Miao, Xixi; Pi, Leilei; Fang, Lei; Wu, Ran; Xiong, Chunhua
Abstract: In this study, a unique carrier magnetic chitosan microspheres (MCTS) was simply synthesized by anchoring Fe3 O4 onto chitosan for direct immobilization of cellulases cross-linked by gluteraldehye. The structure and morphology were characterized using FT-IR, TGA, VSM and SEM. The optimum immobilization conditions were investigated: immobilized pH 7.0, amount of enzyme 15 mL (0.1 mg/mL), immobilization temperature 30 °C, immobilization time 5 h. At optimum conditions, MCTS achieved maximum enzyme solid loading rate of 73.5 mg/g, while recovery of enzyme activity approached to 71.6%. In the recycle test, immobilized cellulases operated without significant loss in its initial performances after 3 cycles, which indicated that immobilized cellulases can be regenerated and reused. The immobilized enzyme has better values of thermal and storage stability than that of free enzyme. Therefore, MCTS may be considered as a candidate with potential value of application in large-scale operations for cellulases immobilization.